Peran Sertifikat Halal dalam Meningkatkan Kepercayaan Konsumen pada Produk Industri Pangan di Indonesia - Dedi Mardianto; Idris Parakkasi; Cut Muthiadin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study explores the role of halal certificates in increasing consumer confidence in food industry products in Indonesia. In a Muslim society and a global market that is increasingly aware of religious ethics and values, halal certificates are not only proof of halalness, but also serve as a signal of quality, safety and integrity of the producer. This research uses a qualitative approach through a literature study, by reviewing scientific articles, books, official reports, and relevant documents related to halal and consumer behavior. The results of the analysis show that halal certificates have three main roles: (1) as a credibility signal to reduce information asymmetry between producers and consumers; (2) as an instrument to reduce risk perceptions of ingredients, processes, and production ethics; and (3) as a brand communication medium that builds emotional attachment and social value. Consumers, especially millennials and Gen Z, demand halalness accompanied by transparency and education in the certification process. Halal certificates also strengthen product competitiveness in the global market, reflecting a religious lifestyle while being modern and sustainable. Therefore, industry players need to make halal certification a comprehensive brand strategy, while regulators such as BPJPH must continue to improve the transparency and effectiveness of the system.